Sociálna produkcia priestoru knižnice - Lacinová, Rebeka (Lidé města, 2025)
The article is based on my bachelor’s thesis, in which I used the ethnographic method to investigate the various aspects that influence the character and activities of a specific library branch. The research aim was to investigate the ongoing social production of library space, examining how different actors, perceptions, relationships, and practices contribute to this process. First, I discuss the physical division of space and its mutual reproduction with organizational structure, whereby highlighting how the librarians’ experience of space can differ from that of readers. Next, I describe the processes of acquiring, placing, organizing, and labelling books, describing how librarians fulfil their roles based on their perceptions of the library and their place within it. After that, I analyze the space in terms of the functions that are embedded in it, linking these conceptions to the roles that books and librarians play within the library. In the final section I deal with the relationships within the library, which are initiated, legitimized, or transformed through the material and character of the space.